3D printed versus commercial models in undergraduate conservative dentistry training. (22nd December 2021) - Richter, Martin; Peter, Thorsten; Rüttermann, Stefan; Sader, Robert; Seifert, Lukas B.
Abstract: Introduction: The treatment of carious lesions is one of the most fundamental competencies in daily dental practice. However, many commercially available training models lack in reality regarding the simulation of pathologies such as carious lesions. 3D printed models could provide a more realistic simulation. This study provides an exemplary description of the fabrication of 3D printed dental models with carious lesions and assesses their educational value compared to commercially available models in conservative dentistry. Materials and Methods: A single‐stage, controlled cohort study was conducted within the context of a curricular course. A stereolithographic model was obtained from an intraoral scan and then printed using fused deposition modelling. These models were first piloted by experts and then implemented and compared against commercial models in a conservative dentistry course. Experts and students evaluated both models using a validated questionnaire. Additionally, a cost analysis for both models was carried out. Results: Thirteen dentists and twenty‐seven 5th year dental students participated in the study. The 3D printed models were rated significantly more realistic in many test areas. In particular, the different tactility and the distinction in colour was rated positively in the 3D printed models. At 28.29€ (compared to 112.36€), the 3D printed models were exceptionally cost‐efficient. Conclusions: 3D printed dental models present a more realistic and cost‐efficient alternative to commercial models in the undergraduate training of conservative dentistry.